The Influence of Using Al-Maktabah Al-Syamilah Software on the Fiqh Learning Ability of Class III Students of the Miftahul Ulum Bettet Pamekasan Islamic Boarding School: Pengaruh Penggunaan Sofware al-Maktabah al-Syamilah Terhadap Kemampuan Belajar Fiqih Santri Kelas III Madrasah Aliyah Diniyah Pondok Pesantren Miftahul Ulum Bettet Pamekasan - Ainur Rofiq, Roisul Ibad; Muliatul Maghfiroh (STAI Terpadu Yogyakarta, 2025)
Al-Maktabah al-Syamilah software can be interpreted as a digital library because it contains books and books that are widely available. Al-Maktabah al-Syamilah is used to find reference sources through the books and books contained therein. The application is used in Islamic Education institutions, especially in Islamic Boarding Schools such as this Miftahul Ulum Bettet Islamic Boarding School which has implemented the use of the Al-Maktabah al-Syamilah Application. This study seeks to analyze whether or not and how much influence the use of Al-Maktabah Al-Syamilah application has on the fiqh learning ability of students in the third grade of Madrasah Aliyah Diniyah Pondok Pesantren Miftahul Ulum Bettet Pamekasan. This research is quantitative in nature and uses data collected from 47 third grade students at Madrasah Aliyah Pondok Pesantren Miftahul Ulum Bettet Pamekasan. Observation and questionnaires were used to collect data. Students were given an assignment to fill out a questionnaire to be completed. The data analysis technique applied is descriptive statistics to identify and explain the problems in this study. In addition, simple linear regression analysis, t-test, and coefficient of determination (R Square) were used. The results of the t-test on the variable use of Al-Maktabah As-Syamilah software showed a significance value of 0.000 < 0.05 and t-count > t-table, with a t-count value of 9.733 and a t-table of 0.281, which indicates a significant relationship between the use of al-maktabah al-syamilah software and Fiqh learning ability. The normality test results indicate that the use of Al-Maktabah As-Syamilah software is normally distributed with a significance value of 0.061 > 0.05, which means that there is a relationship between the use of this software and the Fiqh learning ability of third grade students of Madrasah Aliyah Diniyah Pondok Pesantren Miftahul Ulum Bettet Pamekasan.